An Experimental Study on the Ecological Support Model of Dentate Row Piles - Yousheng Deng; Zhihe Cheng; Mengzhen Cai; Yani Sun; Chengpu Peng (Advances in Materials Science and Engineering)
Bamboo is highly renewable and biodegradable with good short-term strength, which meets the requirement for temporal support structures in shallow foundation pits. Based on this, we conducted a laboratory model test on the dentate bamboo micropile support structure combined with environmentally friendly building materials and new type of piles, to explore the stress characteristics, stress change regularity, and the support effect of the system in soft soil foundation pits. The results show that the earth pressure on the pile sides above the excavation surface gradually decreases with an increase in the excavation depth. The bending deformation of the bamboo pile was also significant. The results also show that the earth pressure and the pile strain below the excavation surface change slightly during the excavation process. When the short sides of the foundation pit were loaded, the highest strain was recorded in the piles 4 and 11. A maximum strain of 358.93 με was recorded, and the maximum displacement of the pile in the top part was obtained to be only 2.14 mm. The most subsidence of dentate pile obtained is only 1.88 mm, whereas that of the single-row pile is 2.35 mm. Compared to the traditional single-row pile, the dentate piles can effectively reduce the horizontal deformation as well as the surface subsidence effectively. They can also support more external lateral load, and hence maintain the foundation stability and give better support. The results provide a theoretical basis for ecological bamboo support technology and have great value to be promoted.